2018
DOI: 10.1093/cid/ciy861
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Impact and Cost-effectiveness of Measles-Mumps-Rubella Vaccination to Prevent Measles Importations Among International Travelers From the United States

Abstract: Background Measles importations and the subsequent spread from US travelers returning from abroad are responsible for most measles cases in the United States. Increasing measles-mumps-rubella (MMR) vaccination among departing US travelers could reduce the clinical impact and costs of measles in the United States. Methods We designed a decision tree to evaluate MMR vaccination at a pretravel health encounter (PHE), compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
(54 reference statements)
0
4
0
4
Order By: Relevance
“…Modeled analyses of various targeted vaccination strategies to mitigate this risk suggested that increased vaccine uptake among schools with the lowest coverage, specifically among individuals with nonmedical exemptions, was projected to have the greatest effect on outbreak potential. Similarly, Hyle et al evaluated the cost-effectiveness of vaccination strategies for international travelers during pretravel health encounters for preventing importation-related measles outbreaks and concluded that targeted vaccination of individuals traveling to destinations with a high risk of measles exposure and those returning to communities with heterogeneous vaccination rates would be expected to provide the most value.…”
Section: Resultsmentioning
confidence: 99%
“…Modeled analyses of various targeted vaccination strategies to mitigate this risk suggested that increased vaccine uptake among schools with the lowest coverage, specifically among individuals with nonmedical exemptions, was projected to have the greatest effect on outbreak potential. Similarly, Hyle et al evaluated the cost-effectiveness of vaccination strategies for international travelers during pretravel health encounters for preventing importation-related measles outbreaks and concluded that targeted vaccination of individuals traveling to destinations with a high risk of measles exposure and those returning to communities with heterogeneous vaccination rates would be expected to provide the most value.…”
Section: Resultsmentioning
confidence: 99%
“…For the United States and other governments concerned with importation of diseases like measles, this work highlights two important priorities. First, reducing the risk contributed by resident travelers is essential, accomplished through increased risk awareness 55 and vaccination coverage 56 among travelers (particularly high-risk travelers and those from communities with heterogeneous vaccination coverage 57 ). Second, this work stresses the tremendous value of information to both domestic biosecurity and global disease control.…”
Section: Discussionmentioning
confidence: 99%
“…We adapted a previously published decision tree (TreeAge, Williamstown MA) for MMR vaccination in travelers and compared 2 strategies among pediatric international travelers: (1) No pretravel health encounter (PHE) and (2) PHE [ 12 ]. Travelers in both strategies begin the simulation with an age-dependent “baseline vaccination status” of 0, 1, or 2 MMR vaccination(s).…”
Section: Methodsmentioning
confidence: 99%